2013
DOI: 10.1371/journal.pone.0059720
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Rice Early Response to Magnaporthe oryzae Identified OsWRKYs as Important Regulators in Rice Blast Resistance

Abstract: Rice blast disease is a major threat to rice production worldwide, but the mechanisms underlying rice resistance to the causal agent Magnaporthe oryzae remain elusive. Therefore, we carried out a transcriptome study on rice early defense response to M. oryzae. We found that the transcriptional profiles of rice compatible and incompatible interactions with M. oryzae were mostly similar, with genes regulated more prominently in the incompatible interactions. The functional analysis showed that the genes involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 71 publications
(86 reference statements)
5
87
2
1
Order By: Relevance
“…Global gene expression profiling has revealed a large number of WRKY genes that are rapidly induced or repressed upon pathogen infection, suggesting that these WRKY genes may contribute to the regulation of rice response to pathogen infection (Ryu et al 2006; Bagnaresi et al 2012; Wei et al 2013). Moreover, some rice WRKY factors have been characterized to be involved in plant defense responses (Pandey and Somssich 2009; Jimmy and Babu 2015; Phukan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Global gene expression profiling has revealed a large number of WRKY genes that are rapidly induced or repressed upon pathogen infection, suggesting that these WRKY genes may contribute to the regulation of rice response to pathogen infection (Ryu et al 2006; Bagnaresi et al 2012; Wei et al 2013). Moreover, some rice WRKY factors have been characterized to be involved in plant defense responses (Pandey and Somssich 2009; Jimmy and Babu 2015; Phukan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic analyses of WRKY gene expression in rice-pathogen interactions have revealed that many WRKY genes are rapidly induced or repressed upon pathogen infection, suggesting that these WRKY genes may contribute to the regulation of rice response to pathogen infection (Ryu et al, 2006;Bagnaresi et al, 2012;Wei et al, 2013). In addition, 13 rice WRKY genes from 12 loci have been characterized to be involved in rice-pathogen interactions.…”
mentioning
confidence: 99%
“…Transcription factors have been identified as important for regulating defensive gene expression (Singh et al, 2002). In our research, WRKY, NAC, AP2/ERF were three types of transcription factors (TFs) detected, all of which were found to participate in the regulation of plant defense genes (Gutterson and Reuber, 2004; Wei et al, 2013; Sun et al, 2015). Two genes (OS06G0649000, OS01G0584900) encoding WRKY TFs were detected with increased transcript accumulation in the treated samples, while no changes were observed in the control samples.…”
Section: Resultsmentioning
confidence: 77%